Various checkpoint molecules, and tumor-infiltrating lymphocytes in common pediatric solid tumors: Possibilities for novel immunotherapy. (2nd January 2019) - Mochizuki, Kazuhiro; Kawana, Satoshi; Yamada, Shoki; Muramatsu, Moe; Sano, Hideki; Kobayashi, Shogo; Ohara, Yoshihiro; Takahashi, Nobuhisa; Hakozaki, Michiyuki; Yamada, Hitoshi; Hashimoto, Yuko; Kikuta, Atsushi
Abstract: Long-term survival rates for pediatric patients with cancer have significantly improved, but novel approaches are desired for those with refractory/relapsed solid tumors. Recently, programed cell death-1/programed cell death-ligand-1 blockade has emerged as an effective option for many intractable cancers. However, not all patients show objective response to such therapy. On the other hand, several other checkpoint pathways, including Herpes virus entry mediator (HVEM)/B- and T-lymphocyte attenuator (BTLA), galectin-9 (GAL9)/T-cell immunoglobulin and mucin domain-3 (TIM3), and major histocompatibility complex class II (MHC-II)/lymphocyte activation gene-3 (LAG3), also regulate immune responses in the tumor microenvironment and may be alternative targets for novel immune therapies. In this study, we examined 65 common pediatric solid tumors and characterized the expression of Herpes virus entry mediator, GAL9, and MHC-II on tumor cells and their corresponding receptors B- and T-lymphocyte attenuator, TIM3, and LAG3, respectively, on tumor-infiltrating lymphocytes (TILs) with immunohistochemistry. Whereas the expression of GAL9 and MHC-II was limited, 73% of rhabdomyosarcomas and 100% of osteosarcomas expressed moderate to high levels of Herpes virus entry mediator on the tumor. TILs were detected in all tumor samples except one osteosarcoma. Interestingly, 45% of rhabdomyosarcomas, and 45% of osteosarcomas expressed moderate to high levels of both Herpes virus entry mediator on the tumor cells and B- and T-lymphocyte attenuator on the TILs. Results showed that a subset of pediatric solid tumors expressed tumor-associated checkpoint molecules, and TILs expressed corresponding receptors for these checkpoint molecules. Thus, immunogenic environments may be created, and checkpoint blockade may induce favorable immune responses.